Coley's immunotherapy revived: Innate immunity as a link in priming cancer cells for an attack by adaptive immunity - Uher, Ondrej; Caisova, Veronika; Hansen, Per; Kopecky, Jan; Chmelar, Jindrich; Zhuang, Zhengping; Zenka, Jan; Pacak, Karel (Seminars in oncology, 2019)
There is no doubt that immunotherapy lies in the spotlight of current cancer research and clinical trials. However, there are still limitations in the treatment response in certain types of tumors largely due to the presence of the complex network of immunomodulatory and immunosuppressive pathways. These limitations are not likely to be overcome by current immunotherapeutic options, which often target isolated steps in immune pathways preferentially involved in adaptive immunity. Recently, we have developed an innovative anti-cancer immunotherapeutic strategy that initially elicits a strong innate immune response with subsequent activation of adaptive immunity in mouse models. Robust primary innate immune response against tumor cells is induced by toll-like receptor ligands and anti-CD40 agonistic antibodies combined with the phagocytosis-stimulating ligand mannan, anchored to a tumor cell membrane by biocompatible anchor for membrane. This immunotherapeutic approach results in a dramatic therapeutic response in large established murine subcutaneous tumors including melanoma, sarcoma, pancreatic adenocarcinoma, and pheochromocytoma. Additionally, eradication of metastases and/or long-lasting resistance to subsequent re-challenge with tumor cells was also accomplished. Current and future advantages of this immunotherapeutic approach and its possible combinations with other available therapies are discussed in this review.
Keywords: Ligands; Immunity, Innate; kombinovaná terapie; Adaptive Immunity; Humans; ligandy; Antineoplastic Agents, Immunological; Toll-Like Receptors; imunitní systém; výsledek terapie; Immune System; lidé; Immunotherapy; zvířata; toll-like receptory; Phagocytosis; fagocytóza; adaptivní imunita; Treatment Outcome; Neoplasms; Tumor Microenvironment; nádory; imunomodulace; nádorové mikroprostředí; Immunomodulation; protinádorové látky imunologicky aktivní; Animals; Combined Modality Therapy; imunoterapie; přirozená imunita